Perinatal Reduced Blood Concentrations of Free Carnitine and Acylcarnitines in Infants with Cystic Fibrosis - Schulpis, Kleopatra H.; Molou, Elina; Manta-Vogli, Penelope; Dotsikas, Yannis; Thodi, Georgia; Chatzidaki, Maria; Loukas, Yannis L. (American Journal of Perinatology, 2019)
Objective Cystic fibrosis (CF) is a multisystemic inherited disease. The aim of this study was to determine free carnitine (FC) and acylcarnitine concentrations in CF newborns with various mutations of the CFTR gene perinatally.Study Design FC/acylcarnitines were determined in dried blood spots via liquid chromatography-tandem mass spectrometry (LC-MS/MS) on the third day of life of full-term normal (n = 50) and CF (n = 28) newborns. For infants with elevated immunoreactive trypsinogen values, FC/acylcarnitines were quantified again 48 hours later, followed by mutational analysis of CFTR gene via Sanger sequencing.Results Initial FC and sums of acylcarnitine concentrations were statistically significantly lower in CF patients than in controls and even lower 48 hours later. The mutations F508del and 621 + 1G > T were predominantly identified among CF patients.Conclusion Low FC and acylcarnitine concentrations were measured perinatally in CF patients, for all CFTR mutations detected. Carnitine supplementation of breastfeeding mothers could be beneficial.
Keywords: cystic fibrosis; CFTR gene; acylcarnitines; newborn screening; fatty acids